Screening for Heavy Metals in Tea Leaves from Bangladesh Using X-Ray Fluorescence - Amber Wolf (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2021)
Trace metal contamination is a global health issue. This study evaluated boxed and loose-leaf tea from Bangladesh using a Handheld X-ray Fluorescence (XRF) analyzer for lead and other metals to rapidly screen tea as a potential hot spot of heavy metal exposure. Of the 33 elements measured, several priority pollutants were below the limit of detection (LOD) in all samples, including lead (LOD 2.17 mg/kg) and arsenic (LOD 1.68 mg/kg). Loose-leaf tea samples had higher copper (1.5-fold), zinc (1.3-fold), and manganese (1.8-fold) concentrations compared to boxed tea. Estimated daily intake (EDI) of lead from tea was calculated using three assumed extractability levels, 20%, 50%, and 100%, and assuming the lead concentration was at the LOD. The EDI for lead ranged from 0.008 µg/kg/bw day to 0.041 µg/kg/bw for adult males and 0.010 µg/kg/bw day to 0.049 µg/kg/bw day for adult females. Based on these tested samples, tea is not likely a primary source of lead exposure in the two sampled areas, Sirajdikhan and Pabna. Future research can evaluate potential processing steps for why some metals were higher in loose-leaf tea compared to boxed tea, including copper, zinc, and manganese. Other potential lead sources could be tested in the tea preparation process, including water sources and dishware used to prepare and consume the tea.
Keywords: Metals; Lead (Pb); Arsenic (As); X-Ray Fluorescence; XRF; Bangladesh